The Effect of Discipline and Motivation on Employee Performance in Micro Small Medium Enterprises (MSMES) Songket Weaving Crafts Aina Silungkang Kota Lunto's Sawah - Rahmad Safitra; Afni Yeni; Ida Nirwana (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of discipline and motivation on the performance of employees of Micro, Small and Medium Enterprises (MSMEs) in Aina Silungkang Songket Weaving Crafts, Sawah Lunto City, with a sample of 40 respondents who were examined using quantitative methods. Based on the results of statistical analysis, it can be interpreted that Discipline partially has a significant effect on Employee Performance, this is evidenced by the t test with a significant value of tcount 4.332 > ttable 2.026 in the significance level value, 0.000 <0.0. So it can be interpreted that the development of Discipline has a significant effect on Employee Performance. Based on the results of statistical analysis, it can be concluded that motivation partially has a significant effect on the performance of employees of Micro, Small and Medium Enterprises (MSMEs) in Aina Silungkang Songket Weaving Crafts, Sawah Lunto City. This is evidenced by the T test with a significant value of tcount 4.588 > t table 2.026 and a significance level value of 0.000 <0.05. So it can be concluded that motivation has a significant effect on employee performance. Simultaneously Discipline and Motivation have a significant effect on Employee Performance of Micro, Small and Medium Enterprises (MSMEs) of Aina Silungkang Songket Weaving Crafts, Sawah Lunto City. This is proven by using the F test with a significant value of fcount 23.934 > ftable 3.25 and the resulting significant value is 0.000 and this value is much smaller than a (0.05). This can also be seen from the R Square value obtained 0.564 or 56.4% and the remaining 43.6% is influenced by other variables not included in this study. Keywords: Discipline, Motivation, Employee Performance